2013
DOI: 10.17146/aij.2012.164
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Degradation Behaviour of Irradiated Bacterial Cellulose Membrane

Abstract: Bacterial cellulose membrane synthesized by Acetobacter xylinum in coconut water medium has potential application for Guided bone Regeneration. However, this membrane may not meet some application requirements due to its low biodegradation properties. In this paper, incorporation of gamma irradiation into the membrane is a developed strategy to increase its biodegradability properties. The in-vitro degradation study in synthetic body fluid (SBF) of the irradiated membrane has been analyzed during periods of 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Hu and Catchmark [ 43 ] suggested that biodegradability could be enhanced by incorporating cellulose-degrading enzymes into the nanostructure of BC. However, these methods are limited by difficulties of controlling biodegradation and potential cytotoxicity due to the presence of residual chemicals in BC [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hu and Catchmark [ 43 ] suggested that biodegradability could be enhanced by incorporating cellulose-degrading enzymes into the nanostructure of BC. However, these methods are limited by difficulties of controlling biodegradation and potential cytotoxicity due to the presence of residual chemicals in BC [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sebelum diaplikasikan di lapangan atau dimanfaatkan oleh petani, perlu dilakukan riset terlebih dahulu mengenai komposisi kompos tablet yang paling tepat dengan aplikasi penambahan hydrogel (Nasution et al, 2019) dan silika serta karakteristik fisik kompos tablet. Penambahan hydrogel (D. Darwis et al, 2011) dimaksudkan agar nutrisi kompos yang tercuci saat pemberian irigasi dapat disimpan sementara waktu sampai digunakan oleh akar tanaman. Sementara penambahan silika limbah geothermal (Wahyudi & Muljani, 2019) letusan Gunung Rinjani dimaksudkan untuk menambah nutrisi mikro ke dalam kompos tablet.…”
Section: A Latar Belakangunclassified
“…BC was prepared using coconut water as a fermentation medium [9][10]. Briefly, the coconut water medium containing 5% (w/v) sucrose and 0.5% (w/v) ammonium sulfate was boiled, and the pH of the medium was adjusted to pH 4 using glacial acetic acid.…”
Section: Preparation Of Bacterial Cellulose (Bc)mentioning
confidence: 99%
“…Bacterial cellulose (BC) has shown promise as a 3D scaffold for bone regeneration because of its high mechanical properties and excellent biocompatibility [6][7][8][9][10][11]. It has been reported that microporous BC supports MC3T3-E1 osteoprogenitor cells to form cell clusters and deposit mineral on the BC, indicating the potential of BC as a 3D scaffold for bone tissue regeneration [6].…”
Section: ■ Introductionmentioning
confidence: 99%